2017
DOI: 10.1016/j.vaccine.2017.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Using the 4 Pillars™ Practice Transformation Program to increase adolescent human papillomavirus, meningococcal, tetanus-diphtheria-pertussis and influenza vaccination

Abstract: Objectives To report the results of an intervention using the 4 Pillars™ Practice Transformation Program (4 Pillars™ Program) to increase adolescent vaccinations including human papillomavirus vaccine (HPV) and influenza vaccines, which remain underutilized in this population. Study Design Eleven pediatric and family medicine practices, previously control sites from a randomized controlled cluster trial, with ≥50 adolescent patients participated. The 4 Pillars™ Program was the foundation of the intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Web-based programs such as the Pillars™ Practice Transformation Program have been shown to be effective in expanding and maintaining vaccine coverage in adolescents. 17 The use of such programs in Turkey may improve the rate of adolescent immunization. Immunization is recommended for adolescents in many countries, but the desired vaccination rates are often not reached.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based programs such as the Pillars™ Practice Transformation Program have been shown to be effective in expanding and maintaining vaccine coverage in adolescents. 17 The use of such programs in Turkey may improve the rate of adolescent immunization. Immunization is recommended for adolescents in many countries, but the desired vaccination rates are often not reached.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk HPV-driven neoplasia can result in the development of several human cancers, of which cervical cancer is the most prevalent. Current HPV vaccines are not therapeutic [1] , uptake has been variable (as low as 40% in the US and France) [ 2 , 3 ], and there remains no targeted antiviral therapy that can clear HPV-associated disease post-infection. High-risk HPVs are typically transmitted by close physical contact, but are stable in the environment and can be transmitted indirectly [4] , either as free virions or as virus-laden epithelial cells (squames) from fomite surfaces such as medical devices [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Uptake of Meningococcal vaccine and Tdap (tetanus, diphtheria and pertussis) vaccine among adolescents has reached healthy people 2020 goals, but HPV vaccine has not. [5] A systematic review showed that adolescents had limited awareness and knowledge of HPV infections and vaccines, even 10 years after the vaccine had become available and they concluded that barriers to the uptake of vaccine needs to be addressed. [6] Since 2006, the vaccine has been approved for use in over 100 countries.…”
Section: Introductionmentioning
confidence: 99%